Riometer Records of 30 MHz Cosmic Noise at Syowa Station, Antarctica in 1973 - ニシムタ, イチゾウ; ヤブウマ, ヒサシ; NISHIMUTA, Ichizo; YABUUMA, Hisashi (National Institute of Polar Research, 1974)
P(論文) departmental bulletin paper